Ślady dawnych gwar typu bułgarskiego w północno-wschodnich Węgrzech - András Zoltán (Ksiegarnia Akademicka Publishing, 2017)
Traces of Old Bulgarian Dialects in North-Eastern Hungary The paper presents the oldest Slavic borrowings in Hungarian together with a reconstruction of the Slavic dialectal landscape of the Carpathian Basin at the time when Hungarian tribes arrived there at the end of the 9th century. According to some phonetic criteria, it seems that Hungarians found two main Slavic dialects in their new homeland: Pannonian Slavic with mixed West and South Slavic features, and Bulgarian Slavic. The dialects of the Bulgarian type might be attributed to today’s north- -eastern Hungary and the neighboring districts of Slovakia.